LANGUAGE SITUATION AND LANGUAGE CONDITION FOR THE EMERGENCE OF BILINGUALISM (Proceedings of International Educators Conference, 2022)
Of all mankind's manifold creations, language must take pride of place. Other inventions - the wheel, agriculture, sliced bread - may have transformed our material existence, but the advent of language is what made us human. Compared to language, all other inventions pale in significance, since everything we have ever achieved depends on language and originates from it. Without language, we could never have embarked on our ascent to unparalleled power over all other animals, and even over nature itself.